IMPLEMENTATION OF PEER LESSONS LEARNING STRATEGY TO IMPROVE STUDENTS LEARNING OUTCOMES SCIENCE ON CLASS V SD - Nurfauziah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This research is motivated by the still weak learning outcomes of science students in grade V of SD Negeri 021 Tarai Bangun. The purpose of this study is to improve student science learning outcomes by implementing peer lessons learning strategies. This type of research uses classroom action research consisting of two cycles. Each cycle consists of four stages, namely: (1) planning; (2) implementation; (3) observation; and (4) reflection. The results of this study showed that the average percentage of student learning outcomes before the action only reached 54.3%. In the first cycle, student learning outcomes increased to 66.6% with a moderate classification, and in the second cycle increased again to 80.5% with a good classification. Based on these results, it can be concluded that implementing peer lessons learning strategies can improve the science learning outcomes of fifth grade students at SD Negeri 021 Tarai Bangun.